Some observations on desiccation in North-Western Nigeria - Prothero, R. Mansell (ERDKUNDE, 1962)
In the northern parts of West Africa, rainfall is low, variable and unreliable. The average population density is low - less than eight inhabitants per square kilometer. In some areas, however, the combination of locally favorable natural factors, especially adequate water supply, with social and historical influences has produced much higher population densities - up to more than 80 inhabitants per sq. km. A characteristic phenomenon of these areas is population movements. There is little evidence of climate deterioration and desert encroachment to the south; however, human impact may cause deterioration of natural conditions. Cultivation methods have not been and are not always sufficiently adapted to the needs of the increasing population and may cause a decrease in soil fertility and soil degradation. These issues are examined in this paper for Sokoto Province in northwestern Nigeria.